Improving Biology Learning with the Use of Blended Learning - Cartono, Cartono (Cattleya Darmaya Fortuna, 2023)
Blended learning is a learning strategy that combines two or more strategies or learning models to achieve expected student learning outcomes. This research aims to evaluate and improve the effectiveness of Biology learning through the application of the Blended Learning method. This research uses a descriptive approach with qualitative methods. The research results show that the application of Blended Learning in Biology learning has a positive impact on student engagement, understanding of Biology concepts, and development of science process skills. Students involved in Blended Learning demonstrate higher levels of participation through online discussions, collaborative projects, and use of online resources. Biology learning materials presented in the form of videos, simulations and virtual practicums increase students' accessibility and motivation for independent exploration. Additionally, the use of Blended Learning allows for a personalized approach tailored to individual students' needs, by monitoring their progress and adapting learning materials. Student communication and collaboration have also been shown to improve through discussion forums and online interactive activities, creating a dynamic and mutually supportive learning environment.